Multipoint radio probe of the solar corona: The trans-coronal radio array fleet - Kooi, Jason E.; Wexler, David B.; Jensen, Elizabeth A.; Wood, Brian E. (Frontiers in Astronomy and Space Sciences, 2022)
The Trans-Coronal Radio Array Fleet (T-CRAF) is a mission concept designed to continuously probe the magnetic field and plasma density structure of the corona at heliocentric distances of ~2-10Rsun (solar radius,Rsun=695,700km). T-CRAF consists of thirty small satellites orbiting the Sun-Earth Lagrange Point L3 in order to provide thirty lines of sight (LOS) for ground- or space-based radio propagation studies. T-CRAF is divided into three sets of orbits, each with ten satellites: the first group provides LOS at a solar offset, SO, (i.e. closest solar approach) of heliocentric distances 2-4Rsun to provide continuous coverage in the middle corona, including initial slow solar wind acceleration; the second group of spacecraft probes the corona at SO=4-7Rsun to cover the region including transition to a supersonic slow solar wind; the outer T-CRAF group is positioned to afford coverage for SO>7Rsun as the winds continue to accelerate towards the Alfvén speed threshold. Each satellite is equipped with a multi-frequency (S-band, C-band, and X-band) linearly polarized transmitter. T-CRAF provides the capability to simultaneously measure the mean values and fluctuations of the magnetic field and plasma density within the solar wind, stream interaction regions, and coronal mass ejections (CMEs). Multiple downlink frequencies provide opportunities to use radio ranging (measurement of group time delay) and apparent-Doppler tracking (measurement of frequency shifts) to infer the plasma density and density gradient along each LOS. Linearly polarized signals provide the ability to detect Faraday rotation (FR) and FR fluctuations, used to infer the magnetic field and field fluctuations along each LOS.